2012
DOI: 10.1073/pnas.1203218109
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor PPARγ-regulated monoacylglycerol O -acyltransferase 1 (MGAT1) expression is responsible for the lipid accumulation in diet-induced hepatic steatosis

Abstract: Recently, hepatic peroxisome proliferator-activated receptor (PPAR)γ has been implicated in hepatic lipid accumulation. We found that the C3H mouse strain does not express PPARγ in the liver and, when subject to a high-fat diet, is resistant to hepatic steatosis, compared with C57BL/6 (B6) mice. Adenoviral PPARγ2 injection into B6 and C3H mice caused hepatic steatosis, and microarray analysis demonstrated that hepatic PPARγ2 expression is associated with genes involved in fatty acid transport and the triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(183 citation statements)
references
References 29 publications
7
169
2
Order By: Relevance
“…This decrease in hepatic steatosis was associated with a decrease in the expression of PPARg and MGAT1. PPARg is a transcriptional factor that participates in hepatic steatosis in rodents (40,41), and PPARg-regulated MGAT1 expression has been described as responsible for lipid accumulation in diet-induced hepatic steatosis (31). SREBP1 and GK expression were downregulated in the HFD-fed PTG OE group.…”
Section: Discussionmentioning
confidence: 96%
“…This decrease in hepatic steatosis was associated with a decrease in the expression of PPARg and MGAT1. PPARg is a transcriptional factor that participates in hepatic steatosis in rodents (40,41), and PPARg-regulated MGAT1 expression has been described as responsible for lipid accumulation in diet-induced hepatic steatosis (31). SREBP1 and GK expression were downregulated in the HFD-fed PTG OE group.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike the pattern observed in G0s2-knockdown 3T3-L1 cells, G0s2-knockout MEF cells accumulate many small lipid droplets during adipogenesis, but these do not mature into the larger lipid droplets observed in wild-type MEFs. Immunoblot analysis of adipocytes at days 6, 9, and 12 revealed that, to some extent, expression levels of PPARg and its regulatory genes, aP2/422, and fatspecific protein 27 21 were reduced in G0s2-knockout MEFs (Figure 7b). The reason why MEFs from G0s2-knockout mice do not exhibit increased caspase 3, as seen in 3T3-L1 cells, is not clear.…”
Section: Role Of G0s2 In Adipogenesis H Choi Et Almentioning
confidence: 99%
“…FAT/CD36, primarily expressed in adipose tissue, is a membrane-bound translocase that facilitates FFA uptake into the cell via diffusion and intracellular trafficking (Abumrad et al 1993). Although FAT/CD36 expression level is typically low in hepatocytes, it is increased with diet-induced obesity (Lee et al 2012). Additionally, hepatic steatosis is largely abolished in CD36 knockout mice (Zhou et al 2008), suggesting that aberrant expression of CD36, along with the resulting increase in FFA uptake in liver, may promote development or increase the severity of hepatic steatosis.…”
Section: Fatty Acid Uptakementioning
confidence: 99%
“…With a high-fat diet, PPARγ transcription is upregulated, resulting in the induction of FABP and CD36 genes and increased fatty acid uptake. Moreover, hepatic PPARγ stimulates the expression of genes involved in TG synthesis, including MGAT1, adipose differentiationrelated protein (ADRP), and fat specific protein 27 (FSP27; Lee et al 2012). Liver-specific disruption of PPARγ or MGAT1 in ob/ob mice improves fatty liver Lee et al 2012;Hasenfuss et al 2014), strongly suggesting that PPARγ and its regulatory pathway is responsible for diet-induced hepatic steatosis.…”
Section: Pparγ and Lipid Signalingmentioning
confidence: 99%
See 1 more Smart Citation